Numerical analysis for thermal–hydraulic characteristics and the laminar two-phase nanofluid flow inside a tube equipped with helically twisted tapes as swirl and turbulence promoters - Iman Kalani (Nature Portfolio, 2021)
Abstract In this study, the numerical simulation of heat transfer of Al2O3-water nanofluid in a pipe equipped with helically twisted tapes is investigated. The volume fraction of nanoparticles in this study is equal to 0, 1, 2, and 3%, and a two-phase mixture method has been used to simulate the nanofluids. The flow regime is laminar in the present study, and Reynolds numbers are Re = 250, 500, 750, and 1000. The helical twisted tapes are in three different types, single, double, and triple. The same heat flux 5000Wm-2 is applied to the walls. The simulation results showed that increasing the Re increases the Nusselt number and decreasing the friction factor. Nusselt number in case 1 and volume fraction of nanoparticles 0% for Re = 250, 500, 750 and 1000 are equal to 95.8, 57.11, 56.13 and 22.15, respectively. The average friction factor is equal to 0.18, 0.09, 0.07, and 0.05. The presence of helical twisted tapes increases the $${\text{Nu}}_{ave}$$ Nu ave . The friction factor due to secondary flows and increases the contact of the fluid and the solid surface, so that the Nusselt number in volume fraction of nanoparticles 0%, Re = 250 for case 1, case 2, case 3, and case 4 are 95.8, 46.10, 58.11, and 51.12, respectively, and the friction factor are 18.0, 29.0, 0.38 and 0.48, respectively.